Work Hardening and Change in Contact Condition of Rolling Contact Surface with Plastic Deformation - Takeshi Yoshimi (Japanese Society of Tribologists, 2009)
Machine designers are sometimes confronted with high contact pressure conditions which generate plastic deformation. However there is no clear design method for such severe condition. We investigate the contact condition in the high contact pressure by using a ball-on-glass disc type test. According to the test results, the following conclusions were obtained. 1) The ratio of calculating contact pressure and the hardness in consideration of working hardness, the number of the ratio is settled about 0.4 for any loading condition. 2) In the condition of high contact pressure generating plastic deformation, the contact pressure converges with constant value according to the work hardening behavior of material.